Prediksi Risiko Kebangkrutan Perusahaan Publik ASEAN: Perspektif RBV-DCT - Aditya Arya Mahardhika; Badingatus Solikhah (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Bankruptcy risk is a critical issue for publicly listed companies as it may threaten business sustainability and undermine investor confidence. This study aims to examine the effects of asset growth, revenue growth, market valuation, property, plant and equipment (PPE), goodwill, and research and development expenditure on bankruptcy risk, proxied by the Altman Z-score, among publicly listed companies in ASEAN countries. The study employs a quantitative approach using secondary data obtained from 1,354 non-financial firms listed in Indonesia, Malaysia, Thailand, Singapore, and the Philippines over the 2015–2023 period, yielding a total of 7,726 firm-year observations. Data were analyzed using a fixed-effects panel regression model. The findings reveal that asset growth and goodwill exert a positive and significant effect on the Altman Z-score, whereas research and development expenditure has a negative and significant effect. Revenue growth demonstrates a marginally positive influence, while market valuation and PPE do not exhibit a significant effect on bankruptcy risk. These results suggest that corporate financial stability is determined not only by financial factors but also by the quality of strategic resources and firms’ adaptive capabilities. The novelty of this study lies in the integration of the Resource-Based View and Dynamic Capabilities Theory perspectives into a bankruptcy prediction framework for publicly listed companies across ASEAN countries.